Pancasila’s Moral Grammar, Critical Digital Nationalism and the Two-Level Game in Indonesia’s Foreign Policy - Permana, Aditya; Prasetyo, Ardian (Badan Pembinaan Ideologi Pancasila, 2025)
This study investigates the intersection of bottom-up democratization and Indonesia’s foreign policy during the August 2025 protests and President Prabowo’s visit to China. The research employs descriptive statistics within a mixed-methods framework, specifically utilizing Quantitative Content Analysis (QCA) for social media data and frequency distribution analysis for questionnaire data. Utilizing Kertzer and Zeitzoff’s framework, the research analyzes 7,139 Instagram comments and 837 survey responses. The findings reveal the rise of “Critical Digital Nationalists” who invoke Pancasila to demand ethical diplomacy. However, digital activism remains structurally limited by symbolic expression and echo chambers. This allows the state to exploit nationalist sentiment for geopolitical pragmatism while ignoring substantive critique. Ultimately, Pancasila serves as a vibrant bottom-up “moral grammar,” yet its policy impact is constrained by the state’s dominance in the two-level game. Thus, the revitalization of Pancasila is needed, but it must move beyond state rhetoric and genuinely integrate these bottom-up ethical aspirations into the practical conduct of Indonesia’s international affairs.